Behavioral risk factors associated with reported tick exposure in a Lyme disease high incidence region in Canada - Cécile Aenishaenslin; Katia Charland; Natasha Bowser; Esther Perez-Trejo; Geneviève Baron; François Milord; Catherine Bouchard (BMC, 2022)
Abstract Background Tick-borne diseases, and especially Lyme Disease (LD), are on the rise in Canada and have been met with increasing public health concern. To face these emerging threats, education on the prevention of tick bites remains the mainstay of public health intervention. The objective of this study was to assess the adoption of preventive behaviors toward tick bites and LD and to investigate the association between behavioral risk factors and reported tick exposure in a Canadian, LD high incidence region (Estrie region, Quebec, Canada). Methods A cross-sectional study was conducted in 2018 which used a telephone questionnaire administered to a random sample of 10,790 adult residents of the study region. Questions investigated tick exposure, LD awareness, attitudes towards LD risk, outdoor and preventive behaviors, as well as antibiotic post-exposure prophylaxis (PEP) treatments in the case of a tick bite. Descriptive and multivariable analyses were carried out, considering the nine administrative subregions and the stratified survey design. Results The sub-regional prevalence of reported tick exposure in the previous year ranged from 3.4 to 21.9%. The proportion of respondents that adopted preventive behaviors varied from 27.0% (tick checks) to 30.1% (tick repellent) and 44.6% (shower after outdoor activities). A minority of respondents (15.9%) that sought healthcare after a tick bite received a PEP treatment. Performing tick checks (Odds ratio = 4.33), time spent outdoors (OR = 3.09) and living in a subregion with a higher public health LD risk level (OR = 2.14) were associated with reported tick exposure in multivariable models. Conclusions This study highlights the low level of adoption of preventive behaviors against tick bites in a region where LD risk is amongst the highest in Canada. This suggests a concerning lack of improvement in LD prevention, as low levels of adoption were already reported in studies conducted in the last decade. Innovative and evidence-based approaches to improve education on ticks and tick-borne diseases and to promote behavior changes are urgently needed in Canada.